Effects of Budesonide and Fluticasone Propionate in Pediatric Asthma Patients - Lin-Yu Kuo; Chih-Hsing Hung; Hsing-I Tseng; Jiunn-Ren Wu; Yuh-Jyh Jong; Yu-Te Chu (Elsevier, 2010)
Cytokines and chemokines play important roles in asthma. However, little information exists on the effects of inhaled corticosteroids on cytokine and chemokine plasma levels in childhood asthma. We compared the pharmaceutical effects of two inhaled corticosteroids used in pediatric patients with mild-to-moderate asthma, budesonide and fluticasone propionate. Methods: Pediatric patients aged 5-18 years old were enrolled in this randomized, open-label, observer-blinded study and received 3 months of treatment with either inhaled budesonide (200 mg/puff) or fluticasone propionate (250 mg/puff), at two puffs per day. Peak expiratory flow (PEF), exhaled nitric oxide, Asthma Control Test (ACT), plasma levels of tumor necrosis factor-a, thymus and activation-regulated chemokine, and interferon-inducible protein 10 were measured before treatment and monthly for 3 months after treatment. Results: There were six patients in the budesonide group, and eight in the fluticasone group. After 3 months, both groups showed improved PEF. In the first month, PEF improved more in the budesonide group than in the fluticasone group, though the difference was not significant. After treatment, ACT scores in both groups were well controlled, except for one patient in the fluticasone group. The fluticasone group had a more significant reduction in exhaled nitric oxide than the budesonide group in the first month. Conclusion: Improvements in lung function were more rapid in the budesonide group than the fluticasone group. However, patients in the fluticasone group had better anti-inflammatory responses than those in the budesonide group. We conclude that each inhaled corticosteroids have its own clinical and laboratory effects.